Morphology, flexural, and thermal properties of sepiolite modified epoxy resins with different curing agents - Nohales, Andres (2006)
A bisphenol A-based epoxy resin was modified with 5 wt% organically modified sepiolite (Pangel B40) and thermally cured using two different curing agents: an aliphatic diamine (Jeffamine D230, D230) and a cycloaliphatic diamine (3DCM). The morphology of the cured materials was established by scanning and transmission electron microscopy analysis. The thermal stability, thermo-mechanical properties, and flexural behaviour of the sepiolite-modified matrices were evaluated and compared with the corresponding neat matrix. The initial thermal decomposition temperature did not change with the addition of sepiolite. The flexural modulus of the epoxy matrix slightly increases by the incorporation of the organophilic sepiolite. The flexural strength of the sepiolite modified resin cured with D230 increased by a 10% while the sepiolite modified resin cured with 3DCM resulted in a lower flexural strength compared with the unmodified resin. The reduced flexural strength was attributed to the stress concentrations caused by the sepiolite modifier, which rendered the resins more brittle.